1996
DOI: 10.1159/000157203
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Morphometrics in Primatology: Craniofacial Variation in Homo sapiens and Pan troglodytes

Abstract: Traditionally, morphometric studies have relied on statistical analysis of distances, angles or ratios to investigate morphometric variation among taxa. Recently, geometric techniques have been developed for the direct analysis of landmark data. In this paper, we offer a summary (with examples) of three of these newer techniques, namely shape coordinate, thin-plate spline and relative warp analyses. Shape coordinate analysis detected significant craniofacial variation between 4 modern human populations, with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
1
30
0
1
Order By: Relevance
“…Our result support earlier studies (e.g., Howells, 1973Howells, , 1989Hennessy and Stringer, 2002;Hanihara, 2000) by showing that the Inuit differ from other regional groups mainly in their facial flatness (Howells, 1973(Howells, , 1989Hennessy and Stringer, 2002); the SW Amerindian group has a more robust and transversely projecting zygomatic region (Hanihara, 2000); Austria/France have narrower faces, retracted zygomatic bones, projecting nasal bones and vertical frontal bones (Howells, 1973(Howells, , 1989Luboga and Wood, 1990;Lynch et al, 1996;Hanihara, 2000;Hennessy and Stringer, 2002); and the Khoisan have smaller facial breadths and heights combined with broad nasal apertures (Howells, 1973), as well as an angled (anteroinferiorly) infraorbital region and projecting zygomatic bones.…”
Section: Discussionsupporting
confidence: 90%
“…Our result support earlier studies (e.g., Howells, 1973Howells, , 1989Hennessy and Stringer, 2002;Hanihara, 2000) by showing that the Inuit differ from other regional groups mainly in their facial flatness (Howells, 1973(Howells, , 1989Hennessy and Stringer, 2002); the SW Amerindian group has a more robust and transversely projecting zygomatic region (Hanihara, 2000); Austria/France have narrower faces, retracted zygomatic bones, projecting nasal bones and vertical frontal bones (Howells, 1973(Howells, , 1989Luboga and Wood, 1990;Lynch et al, 1996;Hanihara, 2000;Hennessy and Stringer, 2002); and the Khoisan have smaller facial breadths and heights combined with broad nasal apertures (Howells, 1973), as well as an angled (anteroinferiorly) infraorbital region and projecting zygomatic bones.…”
Section: Discussionsupporting
confidence: 90%
“…Although several studies have found differences in the results achieved by traditional and landmark-based morphometric methods (Adams & Funk, 1997;Monteiro & Abe, 1999;Monteiro-Filho et al 2002;Reis et al 2002), other examples show that linear and landmark-based descriptors appear to be effective at capturing major shape features and describing intergroup differentiation (Lynch et al 1996;Navarro et al 2004). Accordingly, the effect of methods on results seems to be related to the type of analysis performed and the amount of within-and between-group variation (Navarro et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, there is a considerable amount of empirical evidence demonstrating the ability of landmark-based geometric methods to provide new insights into patterns of biological shape variation that could not be evaluated by traditional methods (Monteiro & Abe, 1999;Reis et al 2002; among others; cf. Lynch et al 1996). For example, in some studies geometric morphometrics methods were able to discriminate groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the seminal work of Bordes [6], Roe [48,49] and Isaac [23] there has been surprisingly little advance in the quantitative morphometric analysis of such artefacts, especially compared to that which has taken place in biological morphometrics (e.g. [4,5,20,29,42,43,67]). Others [2,53] have suggested that quantitative techniques of shape analysis employed in biology have moved on to such a great extent in recent decades, that a veritable 'revolution' has taken place.…”
Section: Introductionmentioning
confidence: 99%